Relationship of Serum IL-12 to Inflammation, Hematoma Volume, and Prognosis in Patients With Intracerebral Hemorrhage - Yazhao Zhang; Yanan Tian; Jianhui Wei; Yi Xiang (Emergency Medicine International)
Objective. Inflammatory cascades and hematomas after intracerebral hemorrhage (ICH) cause brain tissue and neuronal damage. Interleukin-12 (IL-12) promotes brain inflammation, and regulates coagulation mediated by red blood cells and platelets. This study was designed to investigate the relationship of serum IL-12 to inflammation, hematoma volume, and prognosis in ICH patients. Methods. We recruited patients with ICH within 12 hours of symptom onset (n = 209) and measured their serum IL-12 levels. Patients with an increased National Institute of Health stroke scale (NIHSS) score ≥4 were defined as early neurological deterioration, and modified rankin scale (mRS) score >2 at 3 months after intracerebral hemorrhage was defined as poor prognosis. Results. Levels of serum IL-12 was positively correlated with the admission of NIHSS scores (r = 0.535, P<0.001), hematoma volume (r = 0.608, P<0.001), serum CRP levels (r = 0.561, P<0.001), and serum TNF-α levels (r = 0.533, P<0.001) in 209 cases ICH patients. Levels of IL-12 in ICH patients with early neurological deterioration (median: 82.9 versus 65.8, P<0.001) or with poor prognosis (median: 79.0 versus 65.3, P<0.001) were all significantly higher than those in other ICH patients. In addition, serum IL-12 levels could be used to differentiate ICH patients at risk for early neurological deterioration with an AUC of 0.788 (95% CI: 0.717–0.858) or ICH patients at risk for suffering from an unfavorable outcome with an AUC of 0.787 (95% CI: 0.722–0.851). Conclusion. Elevated admission serum IL-12 levels are closely related to the inflammation, hematoma volume, and prognosis in ICH patients. Substantializing serum IL-12 levels is a prognostic biomarker for ICH.